Requirements for designing a robotic system for aircraft wing fuel tank inspection - Dhoot, Manpreet Kaur; Fan, Ip-Shing; Avdelidis, Nicolas Peter (PHM Society, 2021)
This paper presents the requirements for a robotic system to carry out inspection of fighter aircraft wing fuel tank, typical of challenging harsh environment. The research investigates the challenging case of fighter aircraft wing tank inspection. The wing shape geometry is highly irregular with very few fixed cartesian reference points. The internal structure is congested with many systems and difficult to manoeuvre within. This paper summarizes the key requirements for inspection robotics for fighter aircraft wing tank inspection. The requirements are presented in three categories; i) Robotic locomotion and navigation imposed by the complex and confined space inside the wing structure, ii) the materials, mechanisms and power sources imposed by the hazardous and potentially explosive environment inside the wing tank and lastly, iii) the inspection sensors and assessment algorithms to detect fuel tank defect and degradation features. The authors focus on the flexibility and mobility challenges to overcome the numerous obstacles within the confined space whilst effectively integrating a visual inspection technique to capture defined defects. The paper starts with an overview of existing maintenance practices, highlighting the implications and challenges of these methods. Their limitations inspire the development of novel robotics to achieve detailed internal inspection of an aircraft wing fuel tank. A design concept is proposed together with the validation test methods.